Upaya Pengembangan E-Government Dalam Pelayanan Publik Pada Dinas Koperasi Dan UKM Kota Malang - Yordan Putra Angguna (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2015)
Abstract: E-Government development efforts in public service in the Department of cooperatives and SMEs of Malang. Technological developments in Indonesia very rapidly today. So technology becomes a necessity that should belong to everyone. As information technology can be utilized per community for daily needs. Therefore, the Government took the opportunity to create a quality service by utilizing information technology, called e-government. the concept of e-government is the provision of public services is good governance. Where all the aspects contained in good governance reflected in e-government. Researchers use qualitative types of descriptive research using model data analysis Miles and Huberman. Location to point the attention of researchers is the Department of cooperatives and SMEs of Malang. Based on the results of the study of e-government service of cooperatives and SMEs Malang has been applied over the past five years and the e-government is at the level of preparation. The efforts made are the Department of cooperatives and SMEs are the following education and training activities of the Department of labor, holding Kominfo contracts and making cooperative database applications. The researchers offer an idea of the process of administering the website and application service which aims to develop e-government is desirable and appropriate to the needs of the community and target stakeholders quickly and precisely. Keywords: development, e-government, public service Â Abstrak: Upaya Pengembangan E-government dalam Pelayanan Publik Pada Dinas Koperasi dan UKM Kota Malang. Perkembangan teknologi di Indonesia sangat pesat pada zaman sekarang. Sehingga teknologi menjadi sebuah kebutuhan yang harus dimiliki setiap orang. Seperti teknologi informasi yang dapat dimanfaatkan setiap masyarakat untuk kebutuhan sehari-hari. Oleh karena itu, pemerintah mengambil peluang menciptakan pelayanan yang berkualitas dengan memanfaatkan teknologi informasi yang disebut e-government. konsep e-government adalah pemberian pelayanan publik yang bersifat good governance. Dimana semua aspek-aspek yang terkandung dalam good governance tercermin dalam e-government. Peneliti menggunakan jenis penelitian deskriptif kualitatif dengan menggunakan model analisis data Miles dan Huberman. Lokasi yang menjadi titik perhatian peneliti adalah Dinas Koperasi dan UKM Kota Malang. Berdasarkan hasil penelitan e-government Dinas Koperasi dan UKM Kota Malang telah diterapkan selama lima tahun dan e-government berada pada tingkat persiapan. Upaya yang dilakukan adalah Dinas Koperasi dan UKM adalah mengikuti kegiatan pendidikan dan pelatihan dari Dinas Kominfo, mengadakan tenaga kerja kontrak dan pembuatan aplikasi database koperasi. Peneliti menawarkan sebuah gagasan yaitu aplikasi website dan proses pemberian pelayanan yang bertujuan untuk mengembangkan e-government yang diinginkan dan tepat sasaran kepada kebutuhan masyarakat maupun stakeholders secara cepat dan tepat. Â Kata kunci: pengembangan, e-government, pelayanan publik